Unraveling incompatibility between wheat and the fungal pathogen Zymoseptoria tritici through apoplastic proteomics - Yang, F.; Li, W.; Derbyshire, Mark; Larsen, M.; Rudd, J.; Palmisano, G. (BioMed Central Ltd., 2015)
Background: Hemibiotrophic fungal pathogen Zymoseptoria tritici causes severe foliar disease in wheat. However, current knowledge of molecular mechanisms involved in plant resistance to Z. tritici and Z. tritici virulence factors is far from being complete. The present work investigated the proteome of leaf apoplastic fluid with emphasis on both host wheat and Z. tritici during the compatible and incompatible interactions. Results: The proteomics analysis revealed rapid host responses to the biotrophic growth, including enhanced carbohydrate metabolism, apoplastic defenses and stress, and cell wall reinforcement, might contribute to resistance. Compatibility between the host and the pathogen was associated with inactivated plant apoplastic responses as well as fungal defenses to oxidative stress and perturbation of plant cell wall during the initial biotrophic stage, followed by the strong induction of plant defenses during the necrotrophic stage. To study the role of anti-oxidative stress in Z. tritici pathogenicity in depth, a YAP1 transcription factor regulating antioxidant expression was deleted and showed the contribution to anti-oxidative stress in Z. tritici ,but was not required for pathogenicity. This result suggests the functional redundancy of antioxidants in the fungus. Conclusions: The data demonstrate that incompatibility is probably resulted from the proteome-level activation of host apoplastic defenses as well as fungal incapability to adapt to stress and interfere with host cell at the biotrophic stage of the interaction.